The Role of Islamic Education Teachers of the Digital Era in Realizing Madani (Civil) Society - Asmaiyah, Nur; Rosalianita, Ressi; Jannah, Laili Nur (Al-Islam : Journal of Religion and Civilization, 2022)
An educator is a spearhead in the process of Islamic education. The method of Islamic education will not work well without the role of the teacher. Institutionally, the progress of an educational institution is more determined by the institution's leadership than by other parties. However, in the learning process and the formation of children's character and closeness to the teacher, it is the most decisive role than the individual and other components in the school. The teacher's significant role has excellent potential in the progress of today's era of globalisation and digitalisation, the increasingly widespread access to information and the increasingly mixed media for spreading propaganda of religious extremism and liberalism due to the digital revolution demands an increase in literacy skills and competencies for PAI digital teachers to be able and ready to work. Respond to technological advances by strengthening digital literacy skills, then apply them in PAI learning characterised by civil society's views.